Principles of language learning and teaching : a course in second language acquisition - Brown, H. Douglas ([Place of publication not identifed] : [publisher not identified], 2014)
The sixth edition of this book offers new ways of viewing and teaching second language acquisition (SLA) based on the latest research. Providing a comprehensive overview of the theoretical viewpoints that have shaped language teaching today, the text explains the pedagogical relevance of SLA research in reader-friendly prose
Chapter1. Language, learning and teaching -- Chapter2. First language acquisition -- Chapter3. Age and acquisition -- Chapter4. Human learning -- Chapter5. Individual differences -- Chapter6, Affective factors -- Chapter7. Language, culture, and identity -- Chapter8. Communicative competence -- Chapter9. Interlanguage -- Chapter10. Sorting through perspectives on SLA .
Includes bibliographical references and index.
Keywords: LANGUAGE STUDY AND TEACHING